Expression of Heparan Sulfate Endosulfatases in the Adult Mouse Brain: Co-expression of Sulf1 and Dopamine D1/D2 Receptors - Miya, Ken; Keino-Masu, Kazuko; Okada, Takuya; Kobayashi, Kenta; Masu, Masayuki (Frontiers in Neuroanatomy, 2021)
The heparan sulfate 6-O-endosulfatases, Sulfatase 1 (Sulf1) and Sulfatase 2 (Sulf2), are extracellular enzymes that regulate cellular signaling by removing 6-O-sulfate from the heparan sulfate chain. Although previous studies have revealed that Sulfs are essential for normal development, their functions in the adult brain remain largely unknown. To gain insight into their neural functions, we used in situ hybridization to systematically examine Sulf1/2 mRNA expression in the adult mouse brain. Sulf1 and Sulf2 mRNAs showed distinct expression patterns, which is in contrast to their overlapping expression in the embryonic brain. In addition, we found that Sulf1 was distinctly expressed in the nucleus accumbens shell, the posterior tail of the striatum, layer 6 of the cerebral cortex, and the paraventricular nucleus of the thalamus, all of which are target areas of dopaminergic projections. Using double-labeling techniques, we showed that Sulf1-expressing cells in the above regions coincided with cells expressing the dopamine D1 and/or D2 receptor. These findings implicate possible roles of Sulf1 in modulation of dopaminergic transmission and dopamine-mediated behaviors.